(untitled) (Heritage, 2023)
Dostoyevsky was high-strung, melancholic, a hypochondriac, a dreamer, a passionate gambler and lover, whose main profession was novel writing. His novels were conceptual, anthropological, philosophical, political, theoretical-sentimental tractates, critical and cognitive reflexions of himself and the others. The writer of hazard who tested the limits, going to extremes, writing for money on credit, in a specific kind of literary slavery and creatively stressful pressure and chronic lack of time. As a great writer, he was not free of vanity, egoism, self-love and triumphancy, exceptional charisma and personal misfortune, a prophet and a saint, a conspirator and a political martyr, who experienced suffering as a sort of salvation, enjoyment and source of spiritual divinity, personal resistance, morality and faith of the small man. Owing to being sentenced to death and pardoned at the very shooting range, through the catharsis of the Siberian casemate, he experienced a change of heart. From a dreamer of Fourier’s social utopianism and a liberal European, he became the writer of the “Russian idea” of national conservatism, an apologist of monarchy and holy Russian Empire – the bearer of the “Eastern question” for the sake of the liberation of humanity. He felt uncomfortable in the West European culture and civilization of nihilism, liberalism, socialism and boredom. However, he did not write out of boredom, but out of the feeling of personal mission and glory, and the mission of the “Russian idea”, the idea of Orthodox Christianity and the revelation of the Russian Christ. Those were his great needs and visions of the literary biography.